2004
DOI: 10.1038/labinvest.3700193
|View full text |Cite
|
Sign up to set email alerts
|

Liver biopsies from human females contain male hepatocytes in the absence of transplantation

Abstract: Fetal cells derived from pregnancy can persist in a woman's blood and tissues for decades and have been implicated in the pathogenesis of autoimmune disease. Transplantation studies based on donor sex mismatch suggest that circulating stem cells can lead to liver regeneration with donor-derived hepatocytes. However, male cells in female liver could derive from pregnancy. We investigated male cells in liver biopsies from women with sons and asked whether they were hematopoietic cells or hepatocytes. Fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 34 publications
4
36
0
4
Order By: Relevance
“…Differences in antibody levels between PTD and TD women have been observed also for the IgG against the other VTP assessed, but such differences never reach levels of significance. To date, initial evidence indicates the existence of correlations between viral infections during pregnancy and PTD (36)(37)(38). By a recently set up experimental mouse model, it has been demonstrated that viral infections can predispose to bacterial infections, which ultimately lead to PTD (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in antibody levels between PTD and TD women have been observed also for the IgG against the other VTP assessed, but such differences never reach levels of significance. To date, initial evidence indicates the existence of correlations between viral infections during pregnancy and PTD (36)(37)(38). By a recently set up experimental mouse model, it has been demonstrated that viral infections can predispose to bacterial infections, which ultimately lead to PTD (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, female recipients who have previously produced male offspring may also harbor XY chromosomes further complicating the interpretation of the presence of XY donor cells. 91 Exclusion of fusion events is necessary to determine the true physiological mechanism of repopulation. Bone marrow cells are known to contribute to endothelial cells, myofibroblasts as well as blood cells in the recipient liver.…”
Section: How Do We Define a Liver Cell?mentioning
confidence: 99%
“…48 During pregnancy, there is evidence that cells with multilineage potential passage between the mother and fetus and can engraft a broad array of tissues in each individual, persisting long after birth. 43,[48][49][50][51] Thus, it is interesting to consider whether the existence of chimerism in human pregnancy may reflect an active process, rather than an accidental event that results from a less than perfect barrier between the mother and fetus. Interestingly, there are situations that have been observed in nature, where cells with multilineage potential traffic between genetically disparate organisms in the same species and establish mixed chimerism.…”
Section: Layered Immunity and Fetal Tolerance: Impact On Fetal Exposumentioning
confidence: 99%